Determinants Of Economic Growth The Sumatra Region In The Economic Model Four Sectors In The New Normal Era - Dwi Widiarsih; Ranti Darwin; Siti Hanifa Sandri (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2023)
This research is a scientific study on the determination of specific economic growth for the Sumatra Island region of Indonesia. The modeling is arranged in the economic equation of four sectors. This research method uses quantitative methods with panel data regression analysis tools for the research data series for the period 2015-2019. The results of the study explain that consumption, investment, and government spending affect the economic growth of Sumatra Island. In addition, exports and imports do not affect the economic growth of Sumatra Island. The economic growth of Sumatra Island is currently feeling the impact of the Covid-19 pandemic. This condition requires the island of Sumatra to continue to carry out social and economic activities. The community is expected to be able to adapt to the new normal life (new normal). The impact of the new normal is now beginning to be felt, which can bring back an economy that previously experienced a decline in economic growth. During the new normal period, it is hoped that the economic activities of these four sectors can revive, including consumption, investment, government spending, exports,and imports.